1997
DOI: 10.1002/(sici)1097-0215(19970207)70:4<375::aid-ijc1>3.0.co;2-t
|View full text |Cite
|
Sign up to set email alerts
|

Epstein-Barr virus-associated Hodgkin's disease: Epidemiologic characteristics in international data

Abstract: Hodgkin's disease (HD) has long been suspected to have an infectious precursor, and indirect evidence has implicated Epstein-Barr virus (EBV), a ubiquitous herpesvirus, as a causal agent. Recent molecular studies using EBER in situ hybridization or latency membrane protein-1 (LMP-1) immunohistochemistry have identified EBV latent infection in up to 50% of HD tumors. However, the epidemiologic features of these cases have not been examined in detail. To explore the epidemiology of EBV-positive HD so as to under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

23
299
1
15

Year Published

1998
1998
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 453 publications
(338 citation statements)
references
References 53 publications
23
299
1
15
Order By: Relevance
“…HL in early childhood is related to Epstein Barr virus (EBV) infections, but in TYAs the predominant subtype is nodular sclerosis, which is associated with a much lower incidence of EBV inclusion within the tumour (Jarrett et al, 1996). HL in older childhood has been related to delayed exposure to infection arising from improved socioeconomic conditions (Glaser et al, 1997). Law et al (2003) found marginal evidence for higher NHL incidence in under-15 year olds in less deprived areas in England and Wales, but was not found here.…”
Section: Discussionmentioning
confidence: 99%
“…HL in early childhood is related to Epstein Barr virus (EBV) infections, but in TYAs the predominant subtype is nodular sclerosis, which is associated with a much lower incidence of EBV inclusion within the tumour (Jarrett et al, 1996). HL in older childhood has been related to delayed exposure to infection arising from improved socioeconomic conditions (Glaser et al, 1997). Law et al (2003) found marginal evidence for higher NHL incidence in under-15 year olds in less deprived areas in England and Wales, but was not found here.…”
Section: Discussionmentioning
confidence: 99%
“…27 Nearly half of all classical Hodgkin's disease and T cell lymphomas have EBER-positive tumor cells, whereas only 5% of diffuse large B cell or anaplastic large cell lymphomas express EBER. 4,5,28 Certain subsets of these lymphomas are more likely than others to harbor EBV, such as nasal T/NK lymphoma ( Table 2). In classes of tumors that are only fractionally associated with EBV, further investigation of the prognostic value of EBV testing is warranted.…”
Section: Eber In Situ Hybridizationmentioning
confidence: 99%
“…Nasopharyngeal carcinomas and posttransplant lymphoproliferative disorders are nearly always EBV-associated, whereas several other tumors, such as Hodgkin's disease, nonHodgkin's lymphoma, lymphoepithelioma-like carcinoma, gastric adenocarcinoma, and several types of sarcoma, are less uniformly EBV-associated. [2][3][4][5][6][7] EBV causes benign transient lymphoproliferative lesions at the time of primary infection, and it is found in a benign lesion of the tongue called oral hairy leukoplakia. 8,9 Patients affected by these benign or malignant diseases may benefit from laboratory detection of EBV to confirm their diagnosis or to monitor disease burden after the initiation of therapy.…”
mentioning
confidence: 99%
“…38 (ii) Differences in gender composition among studies may be relevant. Although primary infection with EBV affects males and females similarly, 39 women are less likely than men to develop EBV-positive HL [8][9][10] and other EBV-related cancers, possibly due to heightened immunologic sensitivity following the transient reactivation of latent EBV in pregnancy. 30,40,41 If such a mechanism impacts control of other etiologically relevant infections, risk patterns could differ between our data and data from populations including males.…”
Section: Discussionmentioning
confidence: 99%
“…7 Nevertheless, the role of EBV in HL etiology remains unresolved as present methods detect evidence of EBV in the tumor cells of only a proportion of HL patients, and this evidence is least common in young adults, for whom the epidemiologic support for a viral association is strongest. [8][9][10] Yet, only a few studies have attempted to reconcile the patterns of EBV tumor-cell presence with factors suggestive of viral etiology, such as childhood social class or infection history. One case series analysis found no association of EBV-defined HL with several childhood social class characteristics, 11 while another identified neighborhood poverty as a risk factor but only in women.…”
mentioning
confidence: 99%